Identifying An Appropriate Strategy To Overcome Barriers Facing Hi-tech Start-ups in the Indian Education Sector - Bharel, Sunny Gaurav (2009)
This report aims at arriving at a winning strategy for a start-up hi-tech firm in the Indian Educational Sector. The report is a prelude to a business plan that follows the report and builds upon the inference of this report. For this purpose, both theoretical and practical aspects of start-up businesses have been identified and pitted against each other to obtain an inference. The report answers why it is lucrative to enter the Indian education market by studying the scenario in the country. It also analyzes key theories of start-up firms. Some entrepreneurs have been interviewed and their statements examined. Key business issues, challenges and strategies of these entrepreneurial firms have been looked into. The report concludes by pairing the results of the literature review or theory with those obtained from practical inference by means of entrepreneurial interviews and combining the best of both worlds, a winning strategy for the start-up firm is introduced towards the end. Research cites that strategies such as Differentiation, Resource Based View and Dynamic Capability building are key to modern day hi-tech start-up businesses. The Indian education sector is opening up for growth with more than 50% players in the market being private and the government’s key focus for the next 5 year plan being education. The added woes of paucity of the number of colleges, lecturers and quality study material is a window of opportunity that can be exploited for exponential growth in this industry in India, at this point of time.